The growing burden of diabetes mellitus in the US elderly population. - Sloan, F; Bethel, M; Ruiz, D; Shea, A; Shea, A; Feinglos, M (2008)
BACKGROUND: The prevalence of diabetes mellitus is growing worldwide. Consequently, there has been increased emphasis on primary and secondary prevention of diabetes. To our knowledge, whether there have been actual improvements in outcomes in the last decade or so has not been documented in a nationally representative sample. METHODS: We undertook this study to examine trends in rates of occurrence of diabetes and its complications in persons older than 65 years in the United States. National longitudinal analysis of Medicare claims and other Medicare program data for persons first diagnosed as having diabetes during 1994 (n=33 164), 1999 (n=31 722), or 2003 (n=40 058) were compared with 2 control groups of persons of approximately equal sample size who were not diagnosed as having diabetes, alternatively during 1994, 1999, or 2003 or for the entire period from 1994 to 1999 or from 1999 to 2004. The main outcome measures were death and complications of diabetes including cardiovascular, cerebrovascular, ophthalmic, renal, and lower extremity events. RESULTS: The annual incidence of diabetes increased by 23% between 1994-1995 and 2003-2004, and prevalence increased by 62%. The mortality rate after diagnosis in persons having diagnosed diabetes decreased by 8.3% compared with that in the control groups. Complication rates among persons diagnosed as having diabetes generally increased or stayed the same compared with those in the control groups during 1994 to 2004 except for ophthalmic diseases associated with diabetes. Rates for some major complications were high; for example, the rate for congestive heart failure in the diabetes group during 1999 to 2004 was 475 per 1000 persons. In some cases, most notably renal events, including the most serious complications, there were increases in prevalence in both the diabetes and control groups. CONCLUSION: The burden of financing and providing medical care for persons older than 65 in the United States having diagnosed diabetes is growing rapidly as a result of increased incidence and, especially, prevalence of diagnosed diabetes, decreased mortality, and overall lack of improvement in rates of complications in persons having diagnosed diabetes.